Lexical-Semantic and Stylistic Richness in the Catholic Bible: Their Contribution to the Language Use - Toma, Emanuela (European Scientific Journal, ESJ, 2026)
Religion has historically exerted a profound influence on language use. At the same time in ancient history, people believed in animals and in idols, but later they started understanding that with a new reality, they needed more ways to express their feelings and the symbols. Concretely, they needed to use the language. It became necessary that, with such a reality of religion, they may have the proper utterances and words to express and to communicate with God. This does mean that the language has absolutely helped the religion to express and make obvious. Religion, too, has enriched the language with new vocabulary, phraseology, and cultural context. This study aims to analyze in a lexical-semantic and stylistic point of view, the impact of religion in the language use, and in the same time to consider the fact that religion contributes to the language, enriching it with words and expressions, which, if religion had not existed, such words and expressions would never be heard and used, as in the written language, as in the spoken one.